Studierea posibilităţii de utilizare a culturilor de alge în calitate de stimulatori ai rizogenezei la plantele decorative [Articol] - Ciubuc, Natalia; Grabco, Nadeja (CEP USM, 2014)
We demonstrate the role of some species of alga in the processes of vegetative replication of ornamental plants. We select plants from genus Begonia, becouse they are widely used and offer diferent tipes of cuttings. It was demonstrated that under the influience of Spirullina platensis roots apear at the end of the first week of the experiment.Nostoc linkia stimulate not only rooting, but also stimulate the buds formation.
Keywords: alge; stimularea rizogenezei; plante ornamentale